THE IMPACT OF MACROECONOMIC INDICATORS UPON SME’S PROFITABILITY - Bekeris, Rokas (Ekonomika, 2012)
Profitability is one of the most volatile company’s financial indicators: it is affected not only by internal but also by external, macro factors. Therefore, this research was aimed at evaluating the macroeconomic impact on SMEs’ profitability. The paper presents the model with the macroeconomic factors affecting the profitability of a SME, which includes the macroeconomic indicators such as population and firms’ number in a country, exports and imports, FDI, GDP, unemployment, inflation, taxes paid, average salary, and several others. The paper also deals with the dynamics of corporate profitability in Lithuania and shows a correlation between macro factors and corporate profitability. Most of the selected macroeconomic indicators such as inflation, average wages, the number of enterprises, the monetary base were found not to be statistically significant and had no strong correlation with corporate profitability. The VILIBOR interbank interest rate changes and the unemployment have the gretest impact on profitability.